ARID1A deficiency promotes mutability and potentiates therapeutic antitumor immunity unleashed by immune checkpoint blockade. (May 2018) - Shen, Jianfeng; Ju, Zhenlin; Zhao, Wei; Wang, Lulu; Peng, Yang; Ge, Zhongqi; Nagel, Zachary; Zou, Jun; Wang, Chen; Kapoor, Prabodh; Ma, Xiangyi; Ma, Ding; et al.
Abstract ARID1A (the AT-rich interaction domain 1A, also known asBAF250a ) is one of the most commonly mutated genes in cancer1, 2 . The majority ofARID1A mutations are inactivating mutations and lead to loss of ARID1A expression3, which makes ARID1A a poor therapeutic target. Therefore, it is of clinical importance to identify molecular consequences of ARID1A deficiency that create therapeutic vulnerabilities inARID1A -mutant tumors. In a proteomic screen, we found that ARID1A interacts with mismatch repair (MMR) protein MSH2. ARID1A recruited MSH2 to chromatin during DNA replication and promoted MMR. Conversely, ARID1A inactivation compromised MMR and increased mutagenesis. ARID1A deficiency correlated with microsatellite instability genomic signature and a predominant C>T mutation pattern and increased mutation load across multiple human cancer types. Tumors formed by an ARID1A-deficient ovarian cancer cell line in syngeneic mice displayed increased mutation load, elevated numbers of tumor-infiltrating lymphocytes, and PD-L1 expression. Notably, treatment with anti-PD-L1 antibody reduced tumor burden and prolonged survival of mice bearingARID1A -deficient but notARID1A -wild-type ovarian tumors. Together, these results suggest ARID1A deficiency contributes to impaired MMR and mutator phenotype in cancer, and may cooperate with immune checkpoint blockade therapy. Loss of mismatch-repair protein ARID1A in cancer correlates with high mutation load & checkpoint blockade response, complementing MSI-based prognosis.